Bilateral neonatal suppurative parotitis: A case report and review of the literature - Marialida Farah; Mikhael Makhoul; Adib Moukarzel; Simon Rassi (Heliyon)
Neonatal suppurative parotitis (NSP) is a rare condition marked by parotid gland inflammation, typically caused by Staphylococcus aureus. This case report describes a 19-day-old male neonate who developed sudden-onset NSP that progressed to bilateral involvement, representing a rare, documented case of bilateral NSP in the Middle East. The condition was managed with targeted intravenous antibiotics (Teicoplanin, Amikacin, and Rifampicin) based on microbiological identification of methicillin-resistant Staphylococcus aureus (MRSA), despite the absence of typical risk factors for MRSA infection. The patient's recovery was uncomplicated, with no recurrence observed. A review of 80 reported cases revealed Staphylococcus aureus as the predominant pathogen, often linked to breastfeeding. This case underscores the critical importance of early diagnosis and tailored antibiotic therapy in managing NSP, which is essential for preventing complications and avoiding the need for surgical intervention.